DESIGN AND DEVELOPMENT OF ONION SEGREGATION MACHINE - Sachin A. Kshirsagar; Shreeyash R. Chavan; Ridham G. Parmar; S. S. Wangikar; K.S. Pukale; A.K. Parkhe; Priyanka Pavaskar (International Journal of Innovations in Engineering Research and Technology, 2022)
Onion is an important vegetable crop which is seasonal in production but grown all over the India. According to journey of market six of bulbs plays an important role in its price large size onion bulbs produced in Gujarat, Maharashtra, Karnataka & Tamilnadu and are exported from Mumbai & Kolkata ports to Dubai, Kuwait, Saudi, Singapore. Small size onion bulbs produced in Karnataka & Andhra is exported from Chennai to Singapore, Srilanka and Other countries while medium bulb type onion stored for long term storage. Roller segregation is fast & accurate but a little damage to bulbs. Literally it is solution over consuming, labor intensive which improves economic considerations of farmer. Grading of onion bulb is usually important steps in processing operations which brings overall improvement not only in Marketing system but also in raising its quality. In India traditional method is followed which is manual segregation. Onion grades were developed but that cost more than usual & is not affordable by ordinary farmers. So, keeping in view we have designed onion segregator based on chain arrangement.